Gen Z’s purchase intention: Does Tiktok’s advertising value impact them? - Vonezyo Yupanzara Dharomesz (Universitas Pendidikan Nasional, 2024)
In the dynamic landscape of modern advertising, social media platforms emerged as pivotal channels for influencing consumer behavior. This study investigated the impact of TikTok advertising on Generation Z's purchase intention in Indonesia, focusing on the factors of informativeness, irritation, entertainment, and trendiness. Through a quantitative survey-based approach with 130 respondents, structural equation modeling was employed to analyze the data. The findings revealed that informativeness positively influenced advertising value, while irritation diminished it. Additionally, entertainment and trendiness enhanced advertising value, ultimately leading to a positive impact on purchase intention. This underscored the significance of crafting engaging and relevant advertisements on TikTok to effectively connect with Generation Z consumers. The study contributed to a deeper understanding of the complexities of advertising value in the digital era and provided insights for marketers to refine their strategies for maximum impact in the evolving digital marketplace. Further research could explore these factors across diverse digital platforms to enrich our understanding of their influence on consumer behavior, particularly among Generation Z, who were avid consumers of online content.